Clinical features and outcomes associated with tracheostomy in congenital diaphragmatic hernia. Issue 1 (10th September 2019) - Al Baroudi, Sahar; Collaco, Joseph M.; Lally, Pamela A.; Harting, Matthew T.; Jelin, Eric B.
Abstract: Introduction: The purpose of this study was to examine the clinical features/outcomes associated with tracheostomy in infants with congenital diaphragmatic hernia (CDH). Methods: The study population consisted of liveborn infants reported to the CDH Study Group registry between 2007 and 2017. Subjects were identified as having a tracheostomy if they were discharged or transferred to another hospital with tracheostomy and/or on mechanical ventilation. Multivariate mixed models were used for analyses. Results: The registry population consisted of 5434 subjects, of whom 230 (4.2%) underwent tracheostomy placement. Only 3830 (70.5%) infants survived until discharge/transfer. The median age of tracheostomy placement was 3.3 months (range, 1.3‐13.4 when known; n = 58 out of 154 survivors). The mortality rate among subjects with tracheostomy was 32.8% with a median of 37 days (range, 8‐189 when known; n = 32 out of 75 deceased) ensuing between tracheostomy placement and death. The clinical features found to be associated with increased odds ratio of tracheostomy placement included male sex, birth weight, 5‐minute APGAR score, defect size, liver in chest, ECMO use, cardiac abnormality, other congenital abnormalities, pulmonary hypertension, and the presence of a feeding tube. There was center variation in the rate of tracheostomy placement, which may be partially accounted for by disease severity, but not center size. Conclusion: There are several clinical features that are associated with increased likelihood of tracheostomy placement. Most deaths in subjects with tracheostomies occurred outside the immediate postoperative period. The utility of a standardized protocol for tracheostomy in infants with CDH should be considered.